In vitro evaluation of 225Ac‐DOTA‐substance P for targeted alpha therapy of glioblastoma multiforme. (23rd April 2018) - Majkowska‐Pilip, Agnieszka; Rius, Maria; Bruchertseifer, Frank; Apostolidis, Christos; Weis, Mirjam; Bonelli, Milton; Laurenza, Marta; Królicki, Leszek; Morgenstern, Alfred
Abstract : Glioblastoma multiforme (GBM) is the most malignant form of brain tumors with dismal prognosis despite treatment by surgery combined with radiotherapy and chemotherapy. The neuropeptide Substance P (SP) is the physiological ligand of the neurokinin‐1 receptor, which is highly expressed in glioblastoma cells. Thus, SP represents a potential ligand for targeted alpha therapy. In this study, a protocol for the synthesis of SP labeled with the alpha emitter 225 Ac was developed and binding affinity properties were determined. The effects of 225 Ac‐DOTA‐SP were investigated on human glioblastoma cell lines (T98G, U87MG, U138MG) as well as GBM stem cells. A significant dose‐dependent reduction in cell viability was detected up to 6 days after treatment. Also, colony‐forming capacity was inhibited at the lower doses tested. In comparison, treatment with the conventional agent temozolomide showed higher cell viability and colony‐forming capacity. 225 Ac‐DOTA‐SP treatment caused induction of late apoptosis pathways. Cells were arrested to G2/M‐phase upon treatment. Increasing doses and treatment time caused additional S‐phase arrest. Similar results were obtained using human glioblastoma stem cells, known to show radioresistance. Our data suggest that 225 Ac‐DOTA‐SP is a promising compound for treatment of GBM. Abstract : 225 Ac‐DOTA‐SP was found to be highly cytotoxic not only towards established GBM cell lines but also to particularly radioresistant GBM stem cells. This radiolabeled peptide has been shown to induce apoptosis and cell cycle arrest in G2/M phase. Targeted alpha therapy with 225 Ac‐DOTA‐SP is a promising approach for treatment of GBM and warrants further investigation in vivo.